Fenomena Larangan Perkawinan Adat Takepek menurut Hukum Islam - Sulhanuddin, Sulhanuddin; Karmuji, Karmuji (HOKI : Journal of Islamic Family Law, 2023)
The customary prohibition on marriage in the month of Takepek or in the Islamic calendar is called the month of zulqa'dah, is still held firmly by some people in Kelompang Gubug Village, even though Islam considers that all months are good for holding marriages. This research wants to find out what factors cause the prohibition to marry in the month of Zulqa'dah. The method used is empirical/field research with a qualitative approach. Sources of data obtained in the form of primary data and secondary data. As for how to obtain data in the field through observation, interviews and documentation. Based on the results of the research conducted, it was revealed that the factors that influence the prohibition of getting married in the month of Takepek/zulqa'dah are, due to following ancestral customs, and some people believe that the month of Takepek is an unlucky month, if you violate this taboo you will be unlucky in your marriage. Therefore, in a review of Islamic law, this practice is included as an act of shirk. Even so, in the month of Takepe/Zulqa'dah, according to some shops, there is no difference with marriages in other months.